The Implementation of BUMDes Management in Sinjai Regency - Wahyuddin Zuhri AK; Sri Rahayu Juniati (Jurnal Ad'ministrare, 2020)
Village-owned enterprises (BUMDes) were built to be self-sufficient and creative villages in improving the welfare of communities in the regions. The purpose of this study was to determine the management of BUMDes in Improving Community Welfare in several villages in Sinjai Regency, especially in East Sinjai District. The data collection technique is done by collecting documents related to research discourse, interviews, and direct observation in the field. Meanwhile, data analysis includes data collection, data reduction, data assessment (grouping primary and secondary data), and interpreting data, which is done by critically analyzing the collected data and finally arriving at a conclusion. Research results were obtained based on research in two villages in the district. East Sinjai Kab. Sinjai shows that the management of BUMDes has not been implemented optimally. From the several efforts that have been implemented, the benefits have not been felt in terms of improving the welfare of the community. This is influenced by several factors including lack of communication between BUMDes managers and the community and with the local village government, in addition to the lack of transparency, managerial capacity, legal standing, and stagnation of savings and loan businesses caused by community indiscipline.